The effects of serum lipids on the in vitro activity of lumefantrine and atovaquone against Plasmodium falciparum - Chotivanich Kesinee; Mungthin Mathirut; Ruengweerayuth Ronnatrai; Udomsangpetch Rachanee; Dondorp Arjen M; Singhasivanon Pratap; Pukrittayakamee Sasithon; White Nicholas J (Malaria Journal, 2012)
Abstract Background Lumefantrine and atovaquone are highly lipophilic anti-malarial drugs. As a consequence absorption is increased when the drugs are taken together with a fatty meal, but the free fraction of active drug decreases in the presence of triglyceride-rich plasma lipoproteins. In this study, the consequences of lipidaemia on anti-malarial drug efficacy were assessed in vitro . Methods Serum was obtained from non-immune volunteers under fasting conditions and after ingestion of a high fat meal and used in standard Plasmodium falciparum in-vitro susceptibility assays. Anti-malarial drugs, including lumefantrine, atovaquone and chloroquine in five-fold dilutions (range 0.05 ng/ml – 1 ug/mL) were diluted in culture medium supplemented with fasting or post-prandial 10% donor serum. The in-vitro drug susceptibility of parasite isolates was determined using the 3 H-hypoxanthine uptake inhibition method and expressed as the concentration which gave 50% inhibition of hypoxanthine uptake (IC 50 ). Results Doubling plasma triglyceride concentrations (from 160 mg/dL to 320 mg/dL), resulted in an approximate doubling of the IC 50 for lumefantrine (191 ng/mL to 465 ng/mL, P < 0.01) and a 20-fold increase in the IC 50 for atovaquone (0.5 ng/mL to 12 ng/ml; P < 0.01). In contrast, susceptibility to the hydrophilic anti-malarial chloroquine did not change in relation to triglyceride content of the medium. Conclusions Lipidaemia reduces the anti-malarial activity of lipophilic anti-malarial drugs. This is an important confounder in laboratory in vitro testing and it could have therapeutic relevance.